Global corporate laboratory in a developing country - the case of a Japanese company in Thailand - Kondo Masayuki, (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
As Japanese companies globalize their operations, they establish R&D (research and development) centers as well as production facilities in developing countries. However, it is extremely rare to establish a global corporate laboratory in a developing country. This paper investigates a unique case of a global corporate laboratory in Thailand as a single case study. The paper clarifies the reasons for this unique case from viewpoints of company global operation, customer relation and the distance between a production site and an R&D site. Then, the paper discusses the issues associated with the management of a global corporate laboratory in a developing country, especially local staffing, and their solutions. Code: 21120701